Estimation of the modulation level of cosmic rays at high energies. Issue 3 (1st March 2021) - Bobik, Pavol; Putis, M; Kolesnyk, Y L; Shakhov, B A
ABSTRACT: In this article, we focus on the modulation of cosmic rays at high energies. The aim is to determine the limits of the ability of the heliosphere to modulate the intensities of cosmic rays in the inner heliosphere. We address the following questions: how large is the variation in cosmic rays intensities at high energies, i.e. close to 50, 100, and 200 GeV and above? What is the maximum energy at which modulation effects can be measured near the Earth? Specifically, we look at the magnitudes of the variation in cosmic rays intensity at 1 au over the period 1990–2012, at high energies. Attention is paid to energies of around 50, 100, and 150 GeV, where we can expect experimental results within the next decade.